(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
The purpose of this research was to carry out the biophysical characterization of the Measles micro-basin, Manabí - Ecuador. For which the secondary information was analyzed and a field trip was carried out; through the application of Geographic Information Systems, thematic maps were elaborated in the ArcGis 10.4 software; and, through the rapid ecological evaluation, species of flora and fauna are identified. The biophysical characteristics of the micro-basin are: a semi-humid mega-thermal tropical climate; depressions such as highly dissected mesas, alluvial terraces, and medium hills; a maximun relief of 300 to 40 meters; crops are predominant in terms of land use; and a risk of flooding of 94.96 hectares will be prolonged; the most common species are domesticated animals or damaged flora, reflecting the vulnerability of native and endemic species. In conclusion, a baseline is presented that will allow managing the resources of the micro-basin to achieve sustainable development.